Study of the efficacy and safety of levofloxacin and amoxicillin clavulanate in patients with acute bacterial sinusitis - A. I. Kryukov; N. L. Kunelskaya; A. V. Gurov; G. N. Izotova; G. N. Yushkina (Медицинский совет, 2014)
Currently in Russia, acute sinusitis is diagnosed in 10 million people every year [1, 2]. 15 to 36 % of in-patients at ENT units are people suffering from sinusitis [3].